Four new orientation relationships of Mg17Al12 phase with magnesium matrix in Mg-8Al-0.5Zn alloys - Feiya Liu; Renlong Xin; Xin Wen; Xinfu Gu; Qing Liu (Journal of Magnesium and Alloys, 2023)
Although the non-basal precipitates, those not parallel to the basal plane, are more effective to block basal slip in Mg-Al alloys, the crystallographic orientation relationship (OR) between these precipitates and the α-Mg matrix has not been well established. In this work, the crystallography of the non-basal Mg17Al12 precipitates in AZ80 alloy was systematically investigated by transmission electron microscopy (TEM). By tilting to a suitable electron beam direction, different kinds of non-basal precipitates were recognized in TEM, and the following four new ORs between the non-basal Mg17Al12 precipitates and the matrix were revealed: OR−1:[21¯1¯0]α//[011¯]β,(011¯1)α//(011)β; OR−2:[21¯1¯0]α//[011¯]β,(0001)α1∘from(41¯1¯)β; OR−3:[21¯1¯0]α//[011¯]β,(0001)α//(011)β, and OR−4:[21¯1¯0]α//[011¯]β,(0001)α//(100)β. Furthermore, these ORs and their habit planes were explained using the edge-to-edge matching model. The findings in this work can provide some guidelines for designing the microstructure of Mg-Al alloys to enhance their precipitation hardening potential.